2011
DOI: 10.3354/meps09268
|View full text |Cite
|
Sign up to set email alerts
|

The exhalant jet of mussels Mytilus edulis

Abstract: The exhalant jet flow of mussels in conjunction with currents and/or other mussels may strongly influence the mussels' grazing impact. Literature values of mussel exhalant jet velocity vary considerably and the detailed fluid mechanics of the near-mussel flow generated by the exhalant jet has hitherto been uncertain. Computational modelling of this phenomenon depends on knowledge of the velocity distribution near the exhalant siphon aperture of mussels to provide appropriate boundary conditions for numerical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 51 publications
4
34
0
Order By: Relevance
“…When M. edulis is stimulated by algal cells, the mussel remains fully open and exploits the filtration potential. The maximum flow rate has been estimated as 2.8 l h −1 for the shell length of 33.5 mm at 11.6°C (Riisgård et al, 2011). Another study (Yamamoto et al, 2013) showed that the maximum flow rates for M. galloprovincialis were almost constant when they were acclimatized at 15, 20 and 24°C.…”
Section: Research Articlementioning
confidence: 98%
See 1 more Smart Citation
“…When M. edulis is stimulated by algal cells, the mussel remains fully open and exploits the filtration potential. The maximum flow rate has been estimated as 2.8 l h −1 for the shell length of 33.5 mm at 11.6°C (Riisgård et al, 2011). Another study (Yamamoto et al, 2013) showed that the maximum flow rates for M. galloprovincialis were almost constant when they were acclimatized at 15, 20 and 24°C.…”
Section: Research Articlementioning
confidence: 98%
“…Intensive studies have been conducted to measure the filtration rate, using either particle clearance or direct measurements of inhalant and exhalant flows (Bayne, 1976;Kiøboe et al, 1980;Riisgård, 2001). The exhalant jet velocity of mussels has been reported in a range of 80-30 mm s −1 for Mytilus (Maire et al, 2007;MacDonald et al, 2009;Riisgård et al, 2011). The introduction of video endoscopy (Ward et al, 1991) has made it possible to conduct in vivo observation of the gills inside the shell, and also to estimate the water flow from movement of microspheres in the seawater.…”
Section: Introductionmentioning
confidence: 99%
“…The camera was fitted with an inverted 20 mm focal length lens (Nikon Corporation, Tokyo, Japan) and a magnifying bellows tube to achieve a field of view ranging between 3.0 and 20.5 mm 2 . For PTV and PIV seeding, we prepared a suspension of TiO 2 particles by suspending a small amount of TiO 2 powder in ethanol and diluting it with filtered sea water, followed by treatment with ultrasound for 1 h, yielding particles smaller than 2 μm (Riisgård et al, 2011). We then added a small amount of the suspension to the aquarium to achieve an appropriate seeding density.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The clearance rate (F CR ) was determined from the exponential decrease in algal concentration as a function of time using the formula (e.g. Riisgård et al [29]):…”
Section: Salinity-changing Rate Experimentsmentioning
confidence: 99%
“…During this laps of time, the decrease (or increase) of the salinity was considered near linear so that the dilution rate (or strengthening rate) was given by the slope of a straight line for salinity versus time in the experimental period where the filtration rate was affected. The mussel shell opening degree (SOD), defined as the distance between the shells just below the exhalant siphon aperture [29], was measured manually from a digital photo by using a ruler placed on the glass wall of the experimental aquarium close to the mussel. Blue mussels, Mytilus edulis, were collected in Great Belt, Denmark, and kept in the nearby Marine Biological Research Centre (SDU) in aerated flow-through tanks supplied with seawater (18 ± 1 psu) until the experiments were performed.…”
Section: Salinity-changing Rate Experimentsmentioning
confidence: 99%